The Nation in the Scaffold. Death Sentence and Gallows Politicization in Colombia: 1800-1910 (2012)
This article analyses the practice of the death sentence in Colombia as punishment semiology and the punitive theater from the end of the colonial system to the beginning of the 20th century. In the same way, it examines the penal judicial ordination changes, which made possible the use of the gallows in Colombia as a social control instrument. Also analyzed is the temporary abolition of the gallows in the Radical system period, its resurgence during the Regeneration system and its political use as an instrument to eliminate their enemies in dificult situations like the Thousand Days War. The article emphasizes the use of the gallows on the State’s behalf as an instrument of a symbolic dissuasion between the population, and the opposition of a real horror pedagogy, in an essential period for the State and Nation development history in the 19th century, to its ultimate elimination in the constitutional reform in 1910.